0
$\begingroup$

Good morning, i have a problem solving this:

Express $a_{0}+a_{1}x+a_{2}x^{2}$ in terms of basis: $1,x-1,x^{2}-1$

I make this:

$c_{1}1+c_{2}(x-1)+c_{3}(x^{2}-1)=c_{1}+c_{2}x-c_{2}+c_{3}x^{2}-c_{3}=0+0x+0x^{2}$

then

$C=\begin{array}{ccc} 1 & 0 & 0\\ -1 & 1 & 0\\ -1 & 0 & 1 \end{array}$

and the matrix change of basis is:

$C^{-1}=\begin{array}{ccc} 1 & 0 & 0\\ -1 & 1 & 0\\ -1 & 0 & 1 \end{array}$

$\Longrightarrow a_{0}(1,-1,-1)+a_{1}x(0,1,0)+a_{2}x^{2}(0,0,1)=a_{0}+a_{1}x+a_{2}x^{2}$

but, the answer is wrong and i don't know how fix it, please help me.

$\endgroup$
2
$\begingroup$

You wrote

$c_{1}1+c_{2}(x-1)+c_{3}(x^{2}-1)=c_{1}+c_{2}x-c_{2}+c_{3}x^{2}-c_{3}=0+0x+0x^{2}$

Change it to

$c_{0}1+c_{1}(x-1)+c_{2}(x^{2}-1)=c_{0}+c_{1}x-c_{1}+c_{2}x^{2}-c_{2}=a_0+a_1x+a_2x^{2}$

and calculate $c_0,c_1,c_2$.

$\endgroup$
  • $\begingroup$ okay man, thanks! $\endgroup$ – Bvss12 May 29 '16 at 16:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.